Nutrient Utilisation and Performance of Murrah Buffalo Calves Fed Palm Press Fibre and Sheanut Cake (Vitellaria paradoxa) Based Complete Diets - Kumar, M. Kishan (Indian Journal of Animal Nutrition, 2017)
Two complete diets (roughage, concentrate ratio, 40: 60) in mash form (R II and R III) were formulated using palm press fibre (20 and 15%) and chopped jowar strover (20 and 25%) as roughage source and sheanut cake (18.5 and 28%) along with locally available concentrate ingredients and compared with conventional ration (R I) (consisting of chopped jowar stover, chopped jowar fodder and concentrate mixture, fed separately) for growth performance, nutrient digestibility and cost economics in graded Murrah buffalo calves for a duration of 180 days. The digestibility of DM, OM, CP, EE, and NFE was higher (P<0.01) and that of CFand fibre fractions was lower (P<0.01) in calves fed on complete diets (R II and R III) compared to conventional ration (R I). The retention of N, Ca and P was higher (P<0.01) on complete diets than conventional ration. The average daily gain of calves was better (P<0.05) in ration R III (494.67g) followed by R II (474.00 g) and R I (415.67 g) and the differences between R III and R I group calves were statistically significant. The feed conversion ratio was higher (P<0.01) in calves given complete rations. The cost of feed per kg weight gain was lower on R III diet by 12.72% compared to conventional ration. The present study indicated that fibrous by-products like palm press fibre (15%) and sheanut cake (28%) could be included in complete diets of growing buffalo calves.